PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, AKUNTABILITAS, TRANSPARANSI, WHISTLEBLOWING PADA PENCEGAHAN FRAUD DALAM PENGELOLAAN DANA DESA - Prabawati, Ni Wayan Sintya; Rasmini, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.05.TAHUN.2024, 2024)
Fraud is a deviant act or unlawful act that is carried out intentionally to gain personal or group benefits that can harm other people or certain parties. This study aims to determine the effect of human resource competence, accountability, transparency, whistleblowing on fraud prevention in managing village funds. This research was conducted in 6 villages in the District of Rendang with a total sampling technique or census. Respondents in this study were 92 people. The data analysis used is multiple linear regression. The results of this study are human resource competence, accountability, transparency, whistleblowing have a positive effect on fraud prevention in managing village funds. The implication of this research is that the existence of human resource competence, accountability, transparency and supported by adequate whistleblowing will be able to improve fraud prevention in managing village funds